2017
DOI: 10.1021/acssuschemeng.7b01481
|View full text |Cite
|
Sign up to set email alerts
|

High Modulus, Strength, and Toughness Polyurethane Elastomer Based on Unmodified Lignin

Abstract: Lignin-based polyurethane elastomers (LPUe) with high stiffness, strength, and toughness were facilely prepared by direct cross-linking of unfunctionized lignin as hard segments and poly­(propylene glycol) tolylene 2,4-diisocyanate terminated (PPGTDI) as soft domains. The effects of lignin molecular weight (3600 and 600 g mol–1) and weight fraction (5–40 wt %) on the thermal and mechanical properties of LPUe were studied. With an increase in lignin content, LPUe exhibited improved thermal stability, and the gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
104
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 141 publications
(109 citation statements)
references
References 49 publications
5
104
0
Order By: Relevance
“…(3,4) Polyurethanes are a class of versatile macromolecules with extraordinary and versatile performances, including excellent elasticity, flexibility, a wide range of hardness, high tearing capacity, good abrasion resistance, and processability. (5)(6)(7)(8) There is high interest in their applications as coatings, (9,10) adhesives, (11,12) air filters, (13,14) protective textiles, (15,16) and sensors. (17,18) Polyurethane elastomers (PUEs) have a special microphase separation structure, which has shown excellent performance (19) and has attracted the interest of researchers for use in damping and vibration isolation.…”
Section: Introductionmentioning
confidence: 99%
“…(3,4) Polyurethanes are a class of versatile macromolecules with extraordinary and versatile performances, including excellent elasticity, flexibility, a wide range of hardness, high tearing capacity, good abrasion resistance, and processability. (5)(6)(7)(8) There is high interest in their applications as coatings, (9,10) adhesives, (11,12) air filters, (13,14) protective textiles, (15,16) and sensors. (17,18) Polyurethane elastomers (PUEs) have a special microphase separation structure, which has shown excellent performance (19) and has attracted the interest of researchers for use in damping and vibration isolation.…”
Section: Introductionmentioning
confidence: 99%
“…used amino acid (such as serine, aspartic acid, and glutamic acid) derived biorenewable diol chain extenders for the synthesis of thermoplastic polyester‐urethane elastomers. Unmodified lignin based polyurethane elastomers with high stiffness, strength, and toughness were prepared by Li et al . Carvone, a component of the oils extracted from caraway seed Carum carvi and spearmint Mentha spicata , is converted to a seven‐membered lactone: carvomenthide.…”
Section: Sustainable Rubbers and Rubber Like Materialsmentioning
confidence: 99%
“…22,23 In addition, the numerous functional groups of lignin, such as phenolic and aliphatic hydroxyl, methoxyl and carbonyl groups, endow it with sufficient reactivity with various compounds. Different studies have shown that incorporation of lignin in PVA hydrogels, 24 epoxy resins 25 and polyurethane products 26 can effectively improve their mechanical properties and increase their renewable content. In addition, as a complex network of different phenylpropane units, lignin provides necessary hydrophobicity to plant cell walls.…”
Section: Introductionmentioning
confidence: 99%